The Annullment of a Marriage Due to Death in a Polygamous Situation - Rochadi, Daffanza Azriel; Sulastri, Sulastri (Universitas Islam Sultan Agung, 2023)
. Marriage is a legal and religious bond between a man and a woman. In positive law in Indonesia, a marriage must be registered to gain legal recognition. However, there are many cases where marriages are carried out without being registered, especially polygamous marriages. This article examines the legal consequences of polygamous marriages when one of the partners dies. In the literature study conducted, it was found that many polygamous marriages red for various reasons, such as bureaucratic obstacles, not understanding the importance of registration, or deliberately avoiding registration to avoid legal consequences. However, when one of the partners dies, problems arise, especially regarding inheritance rights and the status of children from the marriage. Under existing law, unregistered marriages can be annulled. However, the annulment of marriages that have been broken up due to death has become a polemic. This is because the bereaved spouse often faces difficulties in accessing their rights, such as inheritance and child custody. This article recommends the importance of education regarding marriage registration and changes in regulations to protect the rights of surviving spouses in polygamous marriages.